HOW TO INFLUENCER AND VIRAL MARKETING INCREASE PURCHASE INTENTION - Sulistio, Elbert; Dewi, Liliana (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
Heaven Scent is a business engaged in the perfumery industry and was established in 2021. Various marketing efforts made by Heaven Scent are promotions using influencer marketing and viral marketing. This study was conducted to determine the effect of influencer marketing and viral marketing on purchase intention in products from Heaven Scent. This type of research uses quantitative method research methods with the population, namely followers of Instagram @heavenscentindonesia. Data collection was carried out by questionnaire by Google Form distributed to Heaven Scent social media followers. Sampling using purposive sampling with a sample size of 100 respondents. The data analysis method used in this research is Statistical Product and Service Solution (SPSS) with multiple linear regression analysis method. The results show that the variables of influencer marketing (X1) and viral marketing (X2) have a significant effect on purchase intention, The conclusion that can be drawn from this study is that influencer marketing and influencer marketing variables affect the purchase intention of Heaven Scent products.